Epidemiology, genotypic diversity and age-specific risk pattern of circulating human papillomavirus in Dhaka City, Bangladesh: a five-year study (2020-2024) - Rahman, M. Arifur; Islam, M. Rafiqul; Hasan, M. Nabil; Ullah, M. Sefaut; Jahan, Israt; Morshed, Rafi A.; Parvez, Masum; Comonichi, Nadia; Aslam, Mohammad (International Journal of Research in Medical Sciences, 2025)
Background: Human papillomavirus (HPV) is among the most prevalent sexually transmitted illnesses globally, particularly with certain high-risk genotypes known as the predominant etiological agents of cervical carcinoma, which remains a considerable public health threat, especially in low- and middle-income countries (LMICs), like Bangladesh. Methods: This study investigated the frequency, characteristics, and distribution of HPV genotypes among women in Dhaka City, Bangladesh, from 2020 to 2024. The HPV genotypes were detected by real-time polymerase chain reaction (PCR) from extracted DNA of cervical swab samples. Results: Among 2049 tested participants, the overall HPV prevalence was 4.01%, with significant temporal variations observed throughout the study period. The highest number of positive cases, 29 (4.71%) out of 587, was recorded in 2024, while 2020 showed the lowest incidence, 1 (2.5%) positive case out of 39 cases. Seasonal analysis revealed higher case numbers during Winter (29%) and Autumn (30%), followed by Summer (26%), with Spring showing the lowest incidence (15%). Age distribution analysis indicated that middle-aged adults (35-50 years) represented the largest group with 37 cases, followed by adults aged 25-34 years (25 cases). The most prevalent genotype combination was HPV 16/31 (55 cases), followed by HPV 18/45 (16 cases). Conclusions: This unique genotype distribution pattern differs from global trends and has important implications for vaccination strategies in Bangladesh. The findings suggest the need for broader-spectrum vaccines and age-specific screening programs, while highlighting the importance of considering seasonal variations in public health interventions.